Health utilities and health‐related quality of life of patients with keratinocyte skin cancers - Louisa G. Gordon; Daniel Lindsay; Catherine M. Olsen; David C. Whiteman (Wiley, 2023)
Abstract Background Health utilities and health‐related quality of life (HRQoL) have not been adequately examined in patients with basal and squamous cell carcinomas (or keratinocyte skin cancers KCs) repeatedly treated for multiple skin cancers and who require ongoing medical surveillance. Objectives Our aim was to assess whether health utilities and HRQoL in an Australian population‐based sample of patients recently treated for multiple KCs were poorer compared to patients with single or no KCs. Methods Selected from the QSkin Study, a cross‐sectional analysis of 680 patients was undertaken involving data linkage of survey and administrative claims data. Health utility was measured using the EuroQol‐5D 5‐level (EQ‐5D‐5L) while HRQoL was assessed using the Basal and Squamous Cell Carcinoma Quality of Life (BaSQoL) instrument. Scores were summarised by sociodemographic and skin cancer profiles and stratified by skin cancer group (i.e., naïve or zero, single, multiple KCs). Generalised linear models with Poisson family and log link functions were used for multivariate analyses. Results The mean EQ‐5D‐5L score was slightly worse for people with multiple KCs (mean: 0.88, SD: 0.14) versus single KCs (mean: 0.90, SD: 0.16) versus none (mean: 0.91, SD: 0.11). Mean scores were not significantly different across skin cancer group after adjustment for number of comorbidities and self‐reported health. BaSQoL domain scores indicated having KCs had little impact on quality of life with mean total scores ranging from 0.27 for the 'appearance' domain to 1.15 for the 'other people' domain out of a maximum (worst) score of 3. Conclusions Even among persons chronically afflicted with multiple KCs and ongoing surgical and nonsurgical treatments, health utility and HRQoL losses were minimal and similar to those people without KCs.